Roughness and wettability of surfaces in boundary lubricated scuffing wear. (January 2016) - Wojciechowski, L.; Kubiak, K.J.; Mathia, T.G.
Abstract: The diversity of multidisciplinary approaches suggests that fundamentals of scuffing require systemic, complex multi-scale and multi-physics analysis of an irreversible process as it is postulated in present study. That is probably one of the reasons of lack of an unequivocal model of this irreversible transitional process from stable more or less lubricated wear to scuffing described only by one or few authors in equation(s) form. Therefore, it is useful to characterize the tribological surface properties in frame of systemic approach looking simultaneously for the optimal compromise between rheological, morphological and physicochemical features of contacting surface׳s layer. Hypothetical role connected to any group of features in the topological approach is elucidated and experimentally confirmed via the wettability, strongly combined with surface roughness and surface free energy. Due to the fact that the free energy is directly related to the surface wettability it can as well affect the scuffing activation process. For scientific and rhetoric reasons some selected results of limited boundary lubrication investigations under double blind trial conditions in case of gear oil with anti-wear (AW) and extreme pressure (EP) additives are elucidated here. The results issued from scuffing tests on AISI 4140 ground steel burnished under different forces in order to generate different surface roughness, residual stresses and surface energy are analyzed. It was stated and numerically correlated that the wettability by lubricating medium influences the scuffing resistance. Additionally, the dependence of wettability on selected parameters of roughness and a time to scuffing activation have been stated. On that basis, it is proposed to reinforce concept of "oleophilic" and "oleophobic" properties of metallic surfaces as autonomous invariants determining the activation of catastrophic wear process under boundary lubricated conditions. Highlights: We proposed double-blind experimental procedure in scuffing investigations. We confirmed the influence of selected roughness parameters on wettability. We found out the direct relationship between the surface roughness and wettability. We recognized the synergy of interactions between wettability and surface polarity. We proposed terms of oleophilic and oleophobic in a context of wettability.